PP069 Health Technology Assessment Of Radium-223 Dichloride In Resistant Metastatic Prostate Cancer. (12th January 2018) - Ferriero, Anna Maria; Sacchini, Dario; Tucci, Marcello; Procopio, Giuseppe; Ricardi, Umberto; Fanti, Stefano; De Vincentis, Giuseppe; Danesi, Romano; Restelli, Umberto; Croce, Davide; Vecchio, Fabio; Bianchi, Cosetta; et al.
Abstract : INTRODUCTION: Metastatic castration-resistant prostate cancer (mCRPC) is an incurable disease and represents a significant clinical, economic, and social burden. The therapeutic scenario of mCRPC has completely changed over the last years with the approval of several treatments (1). Radium-223 is a new target-alpha therapy showing a significant survival benefit in mCRPC patients (2, 3). The study aimed to evaluate the introduction of radium-223 in Italy using Health Technology Assessment methodology. METHODS: To assess epidemiological, clinical, economic, organizational, social, and ethical aspects, a literature review was carried out. A cost-effectiveness and a budget impact analysis were performed from the National Health Service (NHS) perspective to compare radium-223 with other treatments and determine the budgetary impact of the utilization of radium-223 for the treatment of mCRPC. RESULTS: In Italy, prostate cancer represents the most diagnosed cancer in men and the third in the whole population. When the disease becomes metastatic, approximately 80 percent of patients develop bone metastases, commonly associated to skeletal-related events (SREs) with a significant impact on survival, quality of life, and costs (1). Radium-223 is a novel alpha particle emitting therapeutic agent which targets new bone growth surrounding bone metastases. Different from other radiopharmaceuticals, radium-223 prolongs overall survival with a favorable safety profile (2, 3). In order to optimize patient outcome, the management of radium-223 should be viewed in a multidisciplinary context. The administration is quite simple and requires only basal shielding. Currently it can be administered in hospital inpatient settings and in some regions the outpatient usage is allowed. Finally, radium-223 showed a favorable budget impact profile and cost-effectiveness when compared with best supportive care and new therapeutic agents (abiraterone, enzalutamide, cabazitaxel) (1). CONCLUSIONS: The introduction of radium-223 allows provision of a new therapy, offering a valid alternative to patient with mCRPC without any increase of costs for the NHS.